Versatile Thermal‐Solidifying Direct‐Write Assembly towards Heat‐Resistant 3D‐Printed Ceramic Aerogels for Thermal Insulation. Issue 5 (28th March 2022) - Wang, Lukai; Feng, Junzong; Luo, Yi; Jiang, Yonggang; Zhang, Guojie; Feng, Jian
Abstract: Ceramic aerogels have great potential in the areas of thermal insulation, catalysis, filtration, environmental remediation, energy storage, etc. However, the conventional shaping and post‐processing of ceramic aerogels are plagued by their brittleness due to the inefficient neck connection of oxide ceramic nanoparticles. Here a versatile thermal‐solidifying direct‐ink‐writing has been proposed for fabricating heat‐resistant ceramic aerogels. The versatility lies in the good compatibility and designability of ceramic inks, which makes it possible to print silica aerogels, alumina‐silica aerogels, and titania‐silica aerogels. 3D‐printed ceramic aerogels show excellent high‐temperature stability up to 1000 °C in air (linear shrinkage less than 5%) when compared to conventional silica aerogels. This improved heat resistance is attributed to the existence of a refractory fumed silica phase, which restrains the microstructure destruction of ceramic aerogels in high‐temperature environments. Benefiting from low density (0.21 g cm –3 ), high surface area (284 m 2 g –1 ), and well‐distributed mesopores, 3D‐printed ceramic aerogels possess a low thermal conductivity (30.87 mW m –1 K –1 ) and are considered as ideal thermal insulators. The combination of ceramic aerogels with 3D printing technology would open up new opportunities to tailor the geometry of porous materials for specific applications. Abstract : A versatile thermal‐solidifying direct‐ink‐writing approach has been proposed for fabricating ceramic aerogels. By the design and optimization of ink compositions, 3D‐printed ceramic aerogels show low thermal conductivity and excellent high‐temperature stability up to 1000 °C. The thermal‐solidifying direct‐write assembly would open up new opportunities to tailor the geometry of ceramic aerogels for specific applications.